Synotis carnosifolia (Asteraceae, Senecioneae), a new species from Yunnan, China - Jin, Zi-Chao; Song, Zhu-Qiu; Guo, Yong-Jie; Chen, You-Sheng (Phytotaxa, 2024)
Synotis carnosifolia (Asteraceae, Senecioneae), a new species from Baoshan in western Yunnan province, China, is described and illustrated. By its habit S. carnosifolia is most closely similar to S. cavaleriei and S. changiana. It differs from S. cavaleriei in its petioles 1–3 cm long, leaf blade elliptical, orbicular or obovate and carnose. It can readily be distinguished from the latter by its leaf blade elliptical, orbicular or obovate, 4–7 × 2–6 cm, carnose in texture, abaxially arachnoid or subglabrous, adaxially glabrous, and blades base rounded. The taxonomic position of the new species within Synotis is also corroborated by evidence from phylogenetic analyses based on ITS and ETS sequence data.